PENGARUH PENGETAHUAN PAJAK DAN SISTEM ADMINISTRASI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (Survei atas WP-OP PBB di KPP Pratama Jakarta Pasar Rebo) - Nazmel Nazir (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2010)
The aims of this research is to make clear the phenomena about the relationship between the degree of tax knowledge, effectiveness of tax administration system and tax compliance. Whereas the objective is to test empirically about this relationship, based on the opinion ofthe individual tax payer ofland and building tax. The method used was verifiable. The source of data was individual tax payer of land and building tax wich formed as population, and the sample were determined by convenience sampling method. Sample data were collected using questionnaire. Data analysis was conducted by correlation and regression analysis. The results showed some empirical evidences that according to individual tax payer opinion: the degree of tax knowledge and the effectiveness of tax administration system, both partially and simultaneously, has (have) positive and significant effect to the tax compliance, Based on those results, it is suggested that the government must have such a mechanism assuring that all the tax rules are known by the tax payer, and that tax administration system must be continuously improved for tax payer convenience.